The Effect of Google Classroom-Based Learning on Written Skills of 10th Graders - Fitri Choirul Muttaqin; Bowo Sugiharto; Harlita Harlita (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2021)
Communication skills are one of the skills that students must have in the Industrial Revolution 4.0. Based on the preliminary study at a public senior high school in Karanganyar, Central Java, students' written skills are still low due to the inaccurate method used by teachers. The applied knowledge that utilizes information and communication technology is needed to improve students' written communication skills. This study aimed to determine the effect of Google classroom-based e-learning on students' written communication skills. This research was a quantitative descriptive study. Students' written skills were measured using the written communication skills assessment instrument developed by Sonseca et al. (2015), which contains ten indicators. The data analysis technique used in this study was the paired sample t-test to compare the results of the pretest and post-test and the N-gain test. The results showed that the correlation value between indicators on the instrument was between 0.388 to 0.567, which means that all indicators used in the research instrument were valid. Besides, Cronbach's alpha value is 0.625, which means that the research instrument is reliable. The pretest means the score was 1.30, and the post-test means the score was 2.85. The results of the paired sample t-test showed a significant value of 0.000, and the results of the N-gain test showed a result of 0.41. Based on the tests' results, there are differences in students' written communication skills between before and after the application of Google classroom-based e-learning.